COVID-19 Transforming postgraduate medical education during the COVID-19 pandemic: creating a trainee-led virtual teaching platform. Issue 1 (2021) - Collins, Emma; Ahmad, Aminah; May, Hannah; Price, Kathryn; Egbase, Elizabeth; Mathews, Catherine
No abstract available